Decision-Making in the Digitalization of Library Reference Services through Social Media: A Case Study of the National Library of Indonesia - Prabowo, Destiya Puji; Maryani, Eni; Bajari, Atwar; Erwina, Wina (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2025)
The digitalization of library reference services through social media remains under-researched, particularly regarding how socio-technical factors and institutional policy processes intersect in national libraries. This study addresses this gap by examining the case of the National Library of Indonesia (Perpusnas), where virtual reference services (VRS) have evolved amid infrastructural reforms and the COVID-19 pandemic. Adopting a qualitative case study within a constructivist paradigm, the research combines semi-structured interviews with librarians and managers (n=5) and a Social Network Analysis (SNA) of @perpusnas1 interactions on X (formerly Twitter) during 2023. The analytical framework integrates the Policy Cycle with the Social Construction of Technology (SCOT), enabling a multi-layered exploration of agenda-setting, policy formulation, interpretive flexibility, and network structures. Findings show that VRS development was shaped by problem recognition (inefficiencies in email services), adaptive policy formulation (iterative SOP revisions and platform selection), and improvisational implementation constrained by staff capacity and infrastructure. SCOT analysis revealed competing interpretations of social media—promotion, reference tool, or user shortcut—eventually stabilised through closure. SNA results confirmed a centralised hub-and-spoke model dominated by @perpusnas1, enhancing responsiveness but limiting distributed participation. This study contributes theoretically by linking SCOT, policy process models, and SNA in library science; practically by highlighting training, evaluation, and integration needs for managers; and for policy by illustrating adaptive pathways to digitalisation in developing-country contexts.